PENGARUH PENGEMBANGAN KARIER DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi pada Sekretariat Daerah Kabupaten Batang) - 11.42.02.0096, Hermanto (Jurnal Mahasiswa Pasca Sarjana, 2013)
Research is done to all employees in the regional Secretariat Batang Regency that has numbers 143 people. From the numbers of employees who become respondent and eligible to be processed were 117 respondent. The purpose of this study is to examine and analyze and employee performance.Based on the validity on the result, all variable have KMO values greater than 0,5 is career development 0,755; work satisfaction is 0,825; organisational commitment is 0,846; and 0,824 for employee performance. So, it can be concluded that the sample had to fulfill adequacy ratio. While the value of loading factor of each indicator variable is greater than 0,4, than it can be declared invalid. Whereas the reliability of test results showing the result of all variables is more than 0,6. So, it can be concluded that the variables used in this study said to be reliable. To test the ability of the model fit and the career development variables in explaining the job satisfaction organizational commitment variables was 55,5%. While variable capabilities career development, job satisfaction and organizational commitment variables in expaining the performance3 of employees is 64,5%.Results of hypothesis testing result show that the whole hypothesis is accepted. It means all independent variables positive and significant effect on the dependent variable. The result also showed that organizational commitment did not mediate influence of career development on employee performance. Similarly, the effect of job satisfaction on employee performance was not mediated by organizational commitment. Key words : career development, job satisfaction, organizational commitment, and employee performance.